Space And Environmental Quality: Analysis Of Impacts In An Amazonian Basin Hydrographic - Santos, Waldemir Lima (2007)
The concern about the environmental quality and the drinkingwaters lock comes reflected from the debates and meetingfulfilled through diverse national and international institutionsthat manage the cause “environment”. Questions as themanage of natural resources in the scope as the hydrographicbasins allied to the human activities give the tone of a possibleshortness, mainly, of hydric resources in the next decades,even to the Amazon region. With this understanding, thepresent work aims at demonstrating the caused environmentalimpacts in the main canal of the hydrographic basin of the waterJudia stream (affluent of the right margim of the river Acre).Cover the urban stretch of the city of Rio Branco/AC aims atdemonstrating, through social-environmental analysis of theoccupants of this area.